2003
DOI: 10.1074/jbc.m211898200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression by Cancer Chemopreventive Dithiolethiones through the Keap1-Nrf2 Pathway

Abstract: Enzyme inducers such as 3H-1,2-dithiole-3-thione (D3T) enhance the detoxication of environmental carcinogens and protect against neoplasia. The putative molecular sensor for inducers is Keap1, a sulfhydrylrich protein that sequesters the transcription factor Nrf2 in the cytoplasm. Expression of these detoxication enzymes is blunted in nrf2-deficient mice; moreover, these mice are more sensitive to carcinogenesis, and the protective actions of dithiolethiones are lost with nrf2 disruption. Hepatic gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
460
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 630 publications
(486 citation statements)
references
References 46 publications
21
460
2
3
Order By: Relevance
“…In line with this, the role of Nrf2 in mediating the co-regulation of the phase II enzymes and ABC transporters was further confirmed by the discovery of AREs (antioxidant response elements) in many of these genes. For example, the AREs have been detected in many genes of the phase II enzymes including the GST (Wasserman and Fahl, 1997;Kwak et al, 2003), GCLC (Kwak et al, 2003), and UGT1A1 genes (Yueh and Tukey, 2007); ARE-like sequences were also identified in the mouse ABCCs (Vollrath et al, 2006). These finding suggest that a common regulatory mechanism is possible for the GST, GCLC and ABCC genes (Meijerman et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…In line with this, the role of Nrf2 in mediating the co-regulation of the phase II enzymes and ABC transporters was further confirmed by the discovery of AREs (antioxidant response elements) in many of these genes. For example, the AREs have been detected in many genes of the phase II enzymes including the GST (Wasserman and Fahl, 1997;Kwak et al, 2003), GCLC (Kwak et al, 2003), and UGT1A1 genes (Yueh and Tukey, 2007); ARE-like sequences were also identified in the mouse ABCCs (Vollrath et al, 2006). These finding suggest that a common regulatory mechanism is possible for the GST, GCLC and ABCC genes (Meijerman et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Since p53 transcript levels were not elevated in compound mutant cells, the accumulation of p53 protein levels may be due to a decrease in protein turnover and may be a major mechanism by which p53 is regulated by its degradation through the ubiquitin-proteosome pathway (37). It is interesting in this regard that a recent gene profiling experiment showed that cancer chemopreventive agent-mediated induction of ubiquitin-proteosome genes was compromised in livers of Nrf2 mutant mice (53). It is therefore possible that down-regulation of the ubiquitin-proteosome pathway plays a part in p53 activation in compound mutant cells.…”
Section: Discussionmentioning
confidence: 97%
“…Although it is not clear at this time how fisetin increases proteasome activity in nerve cells, the time-and substrate-dependence of its effects suggest that fisetin may have both direct and indirect actions on proteasome activity. Many of the protein components of the proteasome are transcriptionally regulated by Nrf2 [47] and Nrf2 inducers can increase proteasome activity in several different cell types [44][45][46]. However, preliminary data suggest that the regulation of proteasome activity by fisetin is likely to be more complex.…”
Section: Fisetin Can Enhance Proteasome Activitymentioning
confidence: 99%